IMPACT OF THE MARKET CONCENTRATION ON TRADING CHAINS’ PERFORMANCE IN SERBIA - Mirović, Vera; Andrašić, Jelena; Kalaš, Branimir (International Journal of Economic Practice and Policy, 2020)
The aim of the paper is testing the difference between the market share of three leading acquired chains and the three leading domestic trading chains in Serbia, as well as the analysis of performance between these two groups of trading chains in the period 2011-2015. Performance of trading chains is measured by profitability, liquidity and leverage indicators. Results of t-test indicate that there is a significant difference between the market share of analyzed trading chains. The analysis of the difference between observed trading chains has shown that there is a significant difference only in the trend of profitability. The correlation analysis between market share and profitability, shows that acquired trading chains with higher market share have lower profitability.